TENUNAN KUBANG DI KECAMATAN GUGUAK KABUPATEN LIMA PULUH KOTA - Marfianda, Wiwi; Ramainas, Ramainas; Adriani, Adriani (Journal of Home Economics and Tourism, 2014)
The purpose of this study was to describe the patterns, materials, weaving techniques and types of products in woven Kubang. This research is descriptive qualitative research method .The type of data in the form of primary and secondary data.The technique of collecting data through observation, interview and documentation. Data analysis techniques with interactive model analysis techniques relating to the subject matter that is the data reduction, data presentation, and conclusion. The results of the research are woven motifs Kubang there are 23 types. The motive there that comes from plants, animals and objects. Thread woven material that is lungsi, and the weft yarn making motive. Weaving technique originally prepare tools and materials. Before the weaving process begins there are some processes that need to be done are: mangumpa, menghani, mengarok, menyuri and connecting threads and menuring. After all the process completed before the weaving process begin. The products produced by the weave Kubang is baju kurung, a skirt, scarf, abaya ,koko ,dress shirt, sarong ,songket and children clothing . Â  Â  Kata kunci: tenunan Kubang, kecamatan guguak